Whole genome sequencing analysis of Komagataeibacter nataicola reveals its potential in food waste valorisation for cellulose production - Muhammad Irhamni Haziqi, Nasharudin; Siew, Shing Wei; Hajar Fauzan, Ahmad; Nazira, Mahmud (Springer Nature B.V., 2024)
Background: Komagataeibacter nataicola (K. nataicola) is a gram-negative acetic acid bacterium that produces natural bacterial cellulose (BC) as a fermentation product under acidic conditions. The goal of this work was to study the complete genome of K. nataicola and gain insight into the functional genes in K. nataicola that are responsible for BC synthesis in acidic environments. Methods and result; The pure culture of K. nataicola was obtained from yeast-glucose-calcium carbonate (YGC) agar, followed by genomic DNA extraction, and subjected to whole genome sequencing on a Nanopore flongle flow cell. The genome of K. nataicola consists of a 3,767,936 bp chromosome with six contigs and 4,557 protein coding sequences. The maximum likelihood phylogenetic tree and average nucleotide identity analysis confirmed that the bacterial isolate was K. nataicola. The gene annotation via RAST server discovered the presence of cellulose synthase, along with three genes associated with lactate utilization and eight genes involved in lactate fermentation that could potentially contribute to the increase in acid concentration during BC synthesis. Conclusion: A more comprehensive genome study of K. nataicola may shed light into biological pathway in BC productivity as well as benefit the analysis of metabolites generated and understanding of biological and chemical interactions in BC production later.